Tingkat Keberdayaan Petani Milenial Penerima Hibah Program YESS - Willie Samodra Laya (Politeknik Negeri Lampung, 2026)
Farmer regeneration is a strategic issue in achieving sustainable agricultural development in Indonesia. The Youth Entrepreneurship and Employment Support Services (YESS) program was introduced to strengthen youth entrepreneurship capacity in the agricultural sector. This study analyzes the empowerment level of millennial farmers receiving competitive grants from YESS using a multidimensional empowerment index, which includes business management, communication and negotiation skills, technology adoption, motivation, and access to capital. A survey was conducted with 59 respondents from West Java, East Java, and South Kalimantan, and the data were analyzed using descriptive statistics, Pearson correlation, and one-way ANOVA. The results show that motivation had the highest average score (4.34), followed by business management (4.29) and communication skills (4.27), while access to capital recorded the lowest score (4.01; SD = 0.68). Pearson correlation analysis revealed strong positive relationships among all empowerment dimensions, with the strongest correlation between management and communication (r = 0.81). ANOVA results indicated no significant differences in empowerment scores based on educational background (F = 1.54; p = 0.2035). These findings highlight that the YESS program has positively contributed to enhancing millennial farmers’ empowerment. However, improving access to financing, continuous mentoring, and building an inclusive agribusiness ecosystem remain essential to ensure the sustainability of agricultural entrepreneurship.